PEMANFAATAN PENULISAN KREATIF SEBAGAI SARANA PROMOSI UMKM KULINER DI DESA CISONTROL, KECAMATAN RANCAH, KABUPATEN CIAMIS, JAWA BARAT - Simatupang, Ervina CM; Rusyan, Susiyanti; Nugraha, Deden Novan Setiawan; Sari , Puspita; Dianita, Dianita; Gunawan, Hero (LPPM Universitas Bina Bangsa, 2024)
In the digital era, technology-based marketing or digital marketing is a breath of fresh air for SMEs, the English Study Program conducted Community Service (PKM) in Cisontrol Village, Ciamis Regency, West Java, which was attended by 20 MSME participants. The purpose of this implementation is to open opportunities for MSMEs to transform into a major economic force. Social media has become the most accessible and utilized digital marketing platform for MSME development, allowing them to reach millions of potential consumers and promote products widely. Digital marketing, which combines interactive and integrated marketing, makes it easier for businesses to understand consumer needs and expand market reach without geographical boundaries. In addition, effective visual design in online marketing can increase consumer interest and trust in influencing purchasing decisions. However, in Cisontrol Village, Ciamis Regency, limited knowledge of marketing technology hinders the promotion of MSME products, especially in the culinary field. Therefore, training on digital promotion strategies and creative writing for wider promotional media is planned, while maintaining existing local values.